DEMENTIA IN DR. SOETOMO GENERAL HOSPITAL SURABAYA: A SYNTHETIC REVIEW OF ITS CHARACTERISTICS - Imami, Nabilah Hasna; Haryono, Yudha; Sensusiati, Anggraini Dwi; Hamdan, Muhammad; Hidayati, Hanik Badriyah (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: Dementia is a clinical syndrome characterized by progressive loss of cognitive function in elderly people interferes the ability to function independently. The number of elderly patients increased so fast in worldwide. The prevalence of dementia rapidly increases due to increasing of population. Aging demographic transition is proceeding rapidly especially in China, India, and Latin America, where dementia is rapidly becoming the major public health problem. Demographic data of elderly patients of dementia in Indonesia is still a little. Dementia’s research data in Indonesia were only obtained from Bali and Yogyakarta, while data from Surabaya were not obtained. Our research data is taken from Dr. General Hospital Soetomo Surabaya, East Java, Indonesia. This study is important for dementia epidemiological data and baseline data for further treatment of dementia patients in Surabaya.Objective: The purpose of this study to determine the characteristics profile of elderly patients with dementia in Dr. Soetomo General Hospital Surabaya, East Java, Indonesia.Methods: Sampling was done with purposive sampling by observing the medical records of patients in the period of January 2017 to December 2017 based on inclusion and exclusion criterias that have been set. The data was taken from the patient's medical record which had been written and examined by neurologists from the neurology department in the neurobehaviour sub-department of Dr. Soetomo Surabaya.Results: The majority of dementia patients are men (51,7%); the age group which is most at risk for dementia is between age of 75-79 years; most of the patients are jobless; more than half of patients are high school graduates; and Vascular Dementia (VaD) is the type of dementia that most people suferredConclusion: This characteristic’s data of dementia can be used for providing information about dementia to make public health care provides a better facillities and treatment for elderly patients to prevent dementia burden.